2010
DOI: 10.1007/s10787-010-0057-1
|View full text |Cite|
|
Sign up to set email alerts
|

Atorvastatin exhibits anti-inflammatory and anti-oxidant properties in adjuvant-induced monoarthritis

Abstract: Arthritis is a joint disorder where the joint damage is associated with elevated levels of inflammatory mediators and reactive oxygen species (ROS). The inflammatory hyperalgesia associated with arthritis has been shown to be attenuated by anti-hyperlipidemic drug, atorvastatin. The present study was carried out to evaluate the effect of atorvastatin on joint inflammation and associated oxidative stress markers in a rat model where arthritis was induced by intra-articular injection of 0.1 ml of 0.1% Freund's C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…The inhibition of prostaglandin E 2 (PGE 2 ) suggests a direct antinociceptive action of simvastatin on nociceptors in peripheral sites similar to that of diclofenac, metamizol or morphine [22]. Supporting this assumption, other studies reported an anti‐inflammatory effect for atorvastatin, comparable to that of diclofenac [23,24]. Furthermore, another explanation for the findings of this work could be the up‐regulation of iNOS expression induced by statins through inhibition of small G protein of the Rho family [25].…”
Section: Discussionsupporting
confidence: 53%
“…The inhibition of prostaglandin E 2 (PGE 2 ) suggests a direct antinociceptive action of simvastatin on nociceptors in peripheral sites similar to that of diclofenac, metamizol or morphine [22]. Supporting this assumption, other studies reported an anti‐inflammatory effect for atorvastatin, comparable to that of diclofenac [23,24]. Furthermore, another explanation for the findings of this work could be the up‐regulation of iNOS expression induced by statins through inhibition of small G protein of the Rho family [25].…”
Section: Discussionsupporting
confidence: 53%
“…In this study, the OVA-challenged animals demonstrated high cellular infiltrate in their bronchial trees, an effect that was significantly reduced by early Atorvastatin treatment. This effect may be related to the anti-inflammatory or the anti-oxidant properties of Atorvastatin previously shown [21,22].…”
Section: Discussionmentioning
confidence: 80%
“…However, the antioxidant and antiinflammatory properties of statins have been known for years. A dose-dependent reduction and normalization of oxidative stress marker levels in joint inflammation has been reported after atorvastatin administration (5). In a recent meta-analysis of 8 randomized trials, the use of short-term statins was associated with a reduction in the incidence of contrast-induced nephropathy, and was recommended even in patients with low LDLcholesterol levels (6).…”
Section: Introductionmentioning
confidence: 99%